Gold Plasmon‐Enhanced Solar Hydrogen Production over SrTiO3/TiO2 Heterostructures. Issue 24 (13th October 2019) - Han, Shitong; Yu, Lisha; Zhang, Hongwen; Chu, Zhengwei; Chen, Xiaofeng; Xi, Hailing; Long, Jinlin
Abstract: This work demonstrated that 75 fold‐enhanced photocatalytic hydrogen production over SrTiO3 /TiO2 heterostructures by Au plasmon‐enhanced electron‐phonon decoupling to generate more amounts of energetic electrons for solar water splitting. Such Au modified SrTiO3 /TiO2 heterostructures were synthesized by a facile hydrothermal post‐photoreduction method, consequently the hydrogen evolution rate is 467.3 μmol g −1  h −1, which is 187 and 75 folds enhancement compared with TiO2 and SrTiO3 /TiO2 samples, respectively. Based on systematic investigations, it is proposed that the internal electric field (IEF) between the interfaces of SrTiO3 /TiO2 and the enhanced near‐field amplitudes of localized surface plasmon (LSP) inhibit the recombination of photogenerated electrons and holes in the bulk and accelerate the interfacial transfer of charge carriers. Simultaneously, electron spin resonance (ESR) showed the change of Ti 3+ species in SrTiO3 /TiO2 microspheres, mirroring the energetic electron transfer process from Au NPs to SrTiO3 /TiO2 microspheres. Abstract : Photocatalysis : 75‐fold enhanced photocatalytic hydrogen production over SrTiO3 /TiO2 heterostructures by the internal electric field (IEF) between the interfaces of SrTiO3 /TiO2 and the enhanced near‐field amplitudes of localized surface plasmon (LSP) inhibit the recombination of photogenerated electrons and holes in the bulk and accelerate the interfacial transfer of charge carriers.